2018
DOI: 10.3390/nu10010065
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Fish Oil Consumption over Other Sources of Lipids on Metabolic Parameters in Obese Rats

Abstract: This study evaluated the effect of the consumption of different levels and sources of lipids on metabolic parameters of Wistar rats. Animals were fed with high-fat diet (HFD) containing 20% of lard for 12 weeks to cause metabolic obesity. Subsequently, the animals were divided into six groups and were fed diets with lipid concentrations of 5% or 20% of lard (LD), soybean oil (SO) or fish oil (FO), for 4 weeks. Data were submitted to analysis of variance (two-way) followed by Tukey post hoc test (p < 0.05). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 58 publications
2
18
0
3
Order By: Relevance
“…The plasma TG concentration was lower in high fat-fed mice with EPA supplementation group than in the high fat diet alone [46]. Recently published data showed that serum TAG, total cholesterol, LDL, and VLDL, in obese Wistar rats fed diets containing 5% or 20% fish oil, was reduced as compared to obese animals fed lard diets, regardless of the concentration [52]. There are only few reports on the Cer and DAG content in high fat-fed animals after fish oil supplementation [15,53].…”
Section: Discussionmentioning
confidence: 99%
“…The plasma TG concentration was lower in high fat-fed mice with EPA supplementation group than in the high fat diet alone [46]. Recently published data showed that serum TAG, total cholesterol, LDL, and VLDL, in obese Wistar rats fed diets containing 5% or 20% fish oil, was reduced as compared to obese animals fed lard diets, regardless of the concentration [52]. There are only few reports on the Cer and DAG content in high fat-fed animals after fish oil supplementation [15,53].…”
Section: Discussionmentioning
confidence: 99%
“…This trend is determined by economic [ 67 ], psychological [ 61 ], religious [ 62 ], health [ 65 , 66 , 68 , 69 ] factors and product availability [ 67 ]. However, the increase in fish consumption leading probably to a decreased incidence of cardiovascular disease (due to long-chain n-3-fatty acids and vitamin D contribution) [ 69 , 70 , 71 , 72 , 73 , 74 ] should be considered with the increased concentrations of environmental toxins (polychlorinated biphenyls, poly and perfluoroalkyl substances and methylmercury) [ 73 , 74 ]. Contaminants detected in fish are associated with cardiovascular diseases, metabolic disorders and cancer [ 74 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study TC, HDL cholesterol and TG plasma levels in rats fed both, low-and high-fat diets with menhaden oil were considerably lower than in rats fed the isocaloric diets based on lard or sunflower oil, and also in animals fed standard chow diet (results not shown). Gondim et al (2018) also demonstrated that supplementation of 10% of energy by fish oil was enough to lower plasma lipid levels. It was also revealed that this hypolipidemic effect increased in line with increasing fish oil content in a diet.…”
Section: Discussionmentioning
confidence: 90%